Comparison of the Serum and Salivary Levels of NT-proBNP in Systemically Healthy Subjects with Mild, Moderate and Severe Chronic Periodontitis - Vijayaraj, Shonali; Ari, Geetha; Rajendran, Sathish; Mahendra, Jaideep; Namasivayam, Ambalavanan (International Journal Of Drug Research And Dental Science, 2022)
Background: To assess and compare the serum and salivary levels of NT-pro BNP in otherwise systemically healthy subjects with mild, moderate, and severe chronic periodontitis. Methods: The subjects for this study were selected from the Out-patient Department of Periodontology, Meenakshi Ammal Dental College and Hospital, Chennai. A total of 24 subjects were selected and divided into three groups which included Group I with6periodontally and systemically healthy subjects, Group II with6 systemically healthy subjects with mild chronic periodontitis, Group III with6 systemically healthy subjects with moderate chronic periodontitis, and group IV with 6 systemically healthy subjects with severe chronic periodontitis. After measuring the periodontal parameters, blood and saliva samples were collected and the levels of NT-proBNP were estimated using an ELISA kit (Abbkine). Results: The mean value of plaque index, modified gingival index, probing pocket depth and clinical attachment level were higher in Group II, Group III, and Group IV compared to Group I. The mean value of NT-proBNP increased with the increasing severity of the periodontal disease. Intergroup comparison of the mean difference of serum and salivary NT-proBNP levels was found to be statistically significant. Karl Pearson correlation analysis between salivary and serum NT-proBNP and other parameters like plaque index, modified gingival index, probing pocket depth, and clinical attachment level showed a very strong positive correlation (P<0.001). Conclusion: Our findings suggest that serum and salivary NT-pro-BNP could serve as a potential biomarker for periodontitis. Further studies are required to explore the mechanism and to understand the cause-effect relationship between NT-proBNP and periodontitis.